Digital Versus Manual Estimation In Construction Budgeting: A Comparative Study - Rehiara, Julianita Adriance Hartini; Tethool, Yoga Charol Vincentius; Puteri, Mayang Kinanti Firstiasya (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Cost estimation is a critical component of construction project planning, often determining a project's financial feasibility and overall success. In Indonesia, the majority of cost estimations are still performed manually using spreadsheets, which are time-consuming and prone to human error. This paper presents a comparative analysis of cost estimation methods applied to a real-world infrastructure project: Pekerjaan Rumah Jaga Bendung Waroser Titik 1 (Construction of a guard house at Waroser Weir – Site 1), located in South Manokwari Regency, Indonesia. The project's RAB (Rencana Anggaran Biaya or Construction Cost Budget Plan) was initially developed using Microsoft Excel and subsequently reconstructed using Estimator.id, a web-based cost estimation platform tailored for the Indonesian construction industry. The comparison focuses on four dimensions: preparation time, accuracy, ease of use, and flexibility in accommodating project adjustments. The results show that Estimator.id significantly reduces processing time, improves calculation accuracy, and simplifies revisions. These findings underscore the potential of digital tools to enhance the efficiency, consistency, and reliability of construction budgeting practices in Indonesia.